2013
DOI: 10.1109/tpel.2013.2251007
|View full text |Cite
|
Sign up to set email alerts
|

EV/PHEV Bidirectional Charger Assessment for V2G Reactive Power Operation

Abstract: This paper presents a summary of the available singlephase ac-dc topologies used for EV/PHEV, level-1 and -2 on-board charging and for providing reactive power support to the utility grid. It presents the design motives of single-phase on-board chargers in detail and makes a classification of the chargers based on their future vehicle-to-grid usage. The pros and cons of each different ac-dc topology are discussed to shed light on their suitability for reactive power support. This paper also presents and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(94 citation statements)
references
References 22 publications
(32 reference statements)
0
94
0
Order By: Relevance
“…Many parametric models are based on real power injections [18,19] considering a power factor equal to 1. Without loss of generality, due to regulatory and operational reasons [20], EVs can be requested to provide voltage and reactive power support. In this case, apparent, real and reactive power are modeled using a non-linear function [21] and a fixed power factor angle φ p Di,t , respectively:…”
Section: Pq and Ev Load Modelingmentioning
confidence: 99%
“…Many parametric models are based on real power injections [18,19] considering a power factor equal to 1. Without loss of generality, due to regulatory and operational reasons [20], EVs can be requested to provide voltage and reactive power support. In this case, apparent, real and reactive power are modeled using a non-linear function [21] and a fixed power factor angle φ p Di,t , respectively:…”
Section: Pq and Ev Load Modelingmentioning
confidence: 99%
“…Application coordination supports not only an efficient integration of renewable energy to the grid power but also inter-EV cooperation for balanced charging. Particularly, trend prediction makes it possible to shift EV charging load, locates the malfunctioning part, and even invites V2G (Vehicle-to-Grid) applications [10].…”
Section: Service Time Analysis For Electric Vehicle Charging Infrastrmentioning
confidence: 99%
“…Recent studies have shown that the battery is not affected due to reactive power operation [11]. Reference [12] have discussed the design, control and assessment of onboard charger reactive power support, however the reactive power support by onboard charger is limited by the mobility and power rating. In [13], the authors managed to supply the reactive power compensation service in a fast charging station and proposed a control strategy for the off-board charger.…”
Section: Introductionmentioning
confidence: 99%